2003
DOI: 10.1046/j.1397-3142.2003.00116.x
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral eosinophilia and eosinophilic gastroenteritis after pediatric liver transplantation

Abstract: Reports indicate peripheral eosinophilia (PE) and gastrointestinal eosinophilic inflammation can occur after pediatric liver transplantation. The incidence of these conditions, potential risk factors, and the impact of PE and gastrointestinal eosinophilic inflammation on liver transplant outcome were determined in this pediatric liver transplant program. Medical records of liver transplant recipients from 1 to 97 and from 12 to 99 were reviewed. Fifty-seven transplants on 54 patients were performed during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
55
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(67 citation statements)
references
References 12 publications
9
55
3
Order By: Relevance
“…Fifty-two of the 163 foods initially avoided were successfully reintroduced, with 17 of the 25 children having been able to reintroduce at least one food to their diet. The tendency for the development of eosinophilic gastrointestinal disease in these patients has been reported by others [31,32]. In the only prospective study to date, Ozbeck et al [33•] observed 28 children with a mean age of 4.96±0.76 years who underwent orthotopic liver transplantation from donors who were not food allergic.…”
Section: Association With Liver Transplantationmentioning
confidence: 77%
“…Fifty-two of the 163 foods initially avoided were successfully reintroduced, with 17 of the 25 children having been able to reintroduce at least one food to their diet. The tendency for the development of eosinophilic gastrointestinal disease in these patients has been reported by others [31,32]. In the only prospective study to date, Ozbeck et al [33•] observed 28 children with a mean age of 4.96±0.76 years who underwent orthotopic liver transplantation from donors who were not food allergic.…”
Section: Association With Liver Transplantationmentioning
confidence: 77%
“…The prevalence of EoE ranged from 2.4% to 3.0% for children post-liver transplantation (26,27). In liver transplant recipients, de novo development of food allergy and gastrointestinal eosinophilic inflammation may be attributed to the potential effect of tacrolimus suppression of T H 1 response and promotion of T H 2 signal pathways (26,(45)(46)(47). The prevalence of EoE was 8% among children with UC (28).…”
Section: Discussionmentioning
confidence: 99%
“…Only younger patients were significantly associated with eosinophilia (Table 1) as has been previously reported. 19 This observation may be linked to the fact that a better SCT prognosis is predicted for younger patients in some genetically based diseases such as congenital immunodeficiency. 20 In conclusion, we have demonstrated that patients with eosinophilia after SCT treatment show an apparently higher survival rate and event-free survival rates compared to those without eosinophilia after SCT.…”
Section: Discussionmentioning
confidence: 99%